Pemanfaatan Limbah Serat Plastik PET Terhadap Kuat Tekan Beton - Renaldi Renaldi; Jasman Jasman; Adnan Adnan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The public greatly anticipates using plastic trash to increase the compressive strength of concrete blocks so they can change form and stop polluting the environment. The purpose of this study is to ascertain how adding PET plastic trash to concrete affects its compressive strengths. Experimental techniques were used in this investigation, including in-lab tests. Afterwards, testing processes in the lab were used to assess the research results. The compressive strength of normal concrete has a value of 25 MPa which reaches the design compressive strength value, while the concrete variation of 1% PET plastic is 23 MPa, 2% PET plastic is 21 MPa, and 3% PET plastic is 19 MPa which does not reach the compressive strength value. plan. This shows that PET plastic waste mixed with concrete results in a decrease in the compressive strength of concrete from normal concrete.